Clinical Profiles, Occurrence, and Management of Adolescent Patients with HAIR-AN Syndrome - Hatim A. Omar; Stephanie Logsdon; Jessica Richards (The Scientific World Journal)
The syndrome of hyperandrogenism, insulin resistance, and acanthosis nigricans (HAIR-AN) is a subphenotype of the polycystic ovary syndrome. It is one of the most common causes of menstrual problems, hyperandrogenic symptoms, and insulin resistance among young women. Review of clinical data in an outpatient adolescent clinic showed that of the 1,002 young women (ages 10—21 years) attending the clinic over a 2-year period, 50 (5%) were diagnosed with HAIR-AN syndrome. Mean age of the patients was 15.5, initial mean weight at diagnosis was 94.5 kg, and the mean BMI was 33.33 kg/m2. Patients were treated with a weight-stabilization and -reduction program, oral contraceptive pills, and in most cases metformin. Of the patients, 80% were compliant with the follow-up and treatment regimen, 60% maintained or reduced their weight, 95% had regular menstrual cycles, and in most patients, the acne and/or hirsutism were the same or better than at the start of treatment. We conclude that HAIR-AN syndrome is a common disease in young women and multifaceted, aggressive treatment appears to be effective in reducing the severity of symptoms and preventing further consequences.